Management of Lentil Rust in Bihar - Sangle, U R; Idris, Md.; Mishra, J S; Bhatt, B P (Indian Farming, 2018)
Rust appeared in epiphytotic form on lentil in whole Mokama Tal area of Bihar during 2014-15 and rust severity ranged from 40-90 % in different fields. At some places total failure was observed during the 2nd week of February. The area gets submerged under deep water monsoon period and becomes unfit for cultivation of kharif crop and cultivation of rabi crops also suffers in productivity due to pests and diseases if water does not recede completely by their sown time, i.e. 15 October.